Human Capital Dan Pengentasan Kemiskinan Dalam Kerangka Ekonomi Islam - Sanusi Gazali Pane (STIKes Ibnu Sina Ajibarang, 2023)
The position of human capital in Islam has a special place and occupies the highest position among other creatures. Although working is not one of the five pillars of Islam, it is an obligation of all capable people and an expression of obedience to God. On the other hand, Allah SWT does not like weakness, even Rasulullah SAW poverty is close to kufr. Thus the role of science and knowledge is very important to improve the human degree from ignorance, backwardness, and poverty. Islam states that the development of knowledgeable human resources is a top priority. Through education, training, and employment opportunities, human capital becomes a valuable asset and a driving force for economic prosperity and independence. On the other hand, for people who are economically disadvantaged, Islam provides a solution in overcoming social inequality through zakat funds. This policy is not only able to alleviate poverty but even improve human dignity with the principles of brotherhood, empathy and social togetherness.